Where is the money? Post-disaster foreign aid flows. (October 2015) - Becerra, Oscar; Cavallo, Eduardo; Noy, Ilan
Abstract This paper describes the flows of aid after large catastrophic natural disasters by using the extensive record of bilateral aid flows, by aid sector, available through the OECD's Development Assistance Committee. For each large donor, the extent of cross-sector reallocation is identified that is occurring in the aftermath of large disasters whereby humanitarian aid increases but other types of aid may decrease. The evidence in this paper suggests that the expectation of large surges in post-disaster aid flows is not warranted given the past diversity of experience of global foreign post-disaster aid by donor and by event. No evidence is found, however, that donors reallocate aid between recipient countries (cross-recipient reallocation). These observations suggest that countries which are predicted to face increasing losses from natural disasters in the coming decades (and almost all are) should be devoting significant resources to prevention, insurance and mitigation, rather than expecting significant post-disaster aid inflows.